Fractional flow reserve guided percutaneous coronary intervention results in reduced ischemic myocardium and improved outcomes. Issue 4 (6th February 2018) - Sawant, Abhishek C.; Bhardwaj, Aishwarya; Banerjee, Kinjal; Jobanputra, Yash; Kumar, Arnav; Parikh, Parth; Kandregula, Krishna C.; Poddar, Kanhaiya; Ellis, Stephen G.; Nair, Ravi; Corbelli, John; Kapadia, Samir
Abstract: Objectives: To determine if fractional flow reserve guided percutaneous coronary intervention (FFR‐guided PCI) is associated with reduced ischemic myocardium compared with angiography‐guided PCI. Background: Although FFR‐guided PCI has been shown to improve outcomes, it remains unclear if it reduces the extent of ischemic myocardium at risk compared with angiography‐guided PCI. Methods: We evaluated 380 patients (190 FFR‐guided PCI cases and 190 propensity‐matched controls) who underwent PCI from 2009 to 2014. Clinical, laboratory, angiographic, stress testing, and major adverse cardiac events [MACE] (all‐cause mortality, recurrence of MI requiring PCI, stroke) data were collected. Results: Mean age was 63 ± 11 years; the majority of patients were males (76%) and Caucasian (77%). Median duration of follow up was 3.4 [Range: 1.9, 5.0] years. Procedural complications including coronary dissection (2% vs. 0%, P = .12) and perforation (0% vs. 0%, P = 1.00) were similar between FFR‐guided and angiography‐guided PCI patients. FFR‐guided PCI patients had lower unadjusted (14.7% vs. 23.2%, P = .04) and adjusted [OR = 0.58 (95% CI: 0.34–0.98)] risk of repeat revascularization at one year. FFR‐guided PCI patients were less likely (23% vs. 32%, P = .02) to have ischemia and had lower (5.9% vs. 21.1%, P < .001) ischemic burden (moderate‐severe ischemia) on post‐PCI stress testing. Presence of ischemia post‐PCI remained a strong predictor of MACE [OR = 2.14 (95%CI: 1.28–3.60)] with worse survival compared to those without ischemia (HR = 1.63 (95% CI: 1.06–2.51). Conclusion: Compared with angiography‐guided PCI, FFR‐guided PCI results in less repeat revascularization and a lower incidence of post PCI ischemia translating into improved survival, without an increase in complications.